Growth responses of microalgae, Chlorella salina and Isochrysis galbana exposed to extracts of the macroalga, Hypnea musciformis - Pramitha, V S; Lipton, A P (Indian Journal of Fisheries, 2012)
The influence of methanol extract and its fractions of the marine macroalga, Hypnea musciformis on aquaculturally important microalgae viz., Chlorella salina and Isochrysis galbana were investigated. Lower concentrations of the extract of H. musciformis resulted in marginal growth gain for C. salina and I. galbana. However, the fractionated extract inhibited the growth of both microalgae tested, suggesting toxicity. Results signify the importance of macroalgal extract in regulating the growth of aquaculturally important microalgae.